On the optimal rate of convergence of the projection-iterative method and some generalizations of it on a class of equations with smoothing operators - Azizov, M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For some classes of operator equations of the second kind with smoothing operators, we find the exact order of the optimal rate of convergence of generalized projection-iterative methods.